SERUM TRACE ELEMENTS (ZINC, COPPER AND MAGNESIUM) IN IRAQI PATIENTS WITH THALASSEMIA MAJOR RECEIVING DESFERRIOXAMINE AND ITS RELATION WITH GROWTH STATE (Iraqi Journal of Medical Sciences, 2016)
Background:Patients with ?-thalassemia major (TM) require periodic blood transfusion and iron-chelating therapy for all their life and they frequently show complications like trace elements abnormalities.Objectives:To evaluate the levels of zinc, copper and magnesium in these patients and to study the relation of these elements with growth state.Methods:Fifty-four patients with TM, with mean age (15.4 years) and age range (7-31) years, and thirty healthy subjects as controls, their mean age (14.7 years) and age range (8-30 years) were included in this case –control study. Each group divided into children and adult groups. Serum levels of zinc, copper and magnesium of all groups were measured calorimetrically. Serum levels of ferritin were measured depending on ELFA technique, in addition to height and weight of all patients and subjects.Results:Mean serum levels of ferritin were significantly elevated in TM patients as compared to controls, while mean serum levels of zinc and magnesium of both patients groups were significantly decreased as compared with control subjects. Mean serum levels of both patients groups were significantly elevated compared to control subjects groups.Conclusion:Patients with TM were suffering from hypozincamia and hypomagnesmia and required additional adjustment, the patients also showed hypercupremia, and there was obvious growth defect in which may be a result of hypozincamia.Keywords: Thalassemia, zinc, height, short-stature
Keywords: Thalassemia; zinc; height; shortstature